Arsenic(V) sorption kinetics in long-term arsenic pesticide contaminated soils. (December 2019) - Rahman, M.S.; Clark, M.W.; Yee, L.H.; Burton, Edward D.
Abstract: Historic As contamination of soils occurs throughout the world from mining, industrial and agricultural activities. Sorption processes and rate may strongly influence soil As mobility, which further influences As bioavailability and toxicity. We investigated the kinetics of As(V) sorption by adding the arsenic onto both pristine (non-contaminated) and historically contaminated soils from arsenicals in two contrasting soil types (ferralitic and sandy). Results suggest both pseudo-second order (PSO) and Elovich kinetic models produce robust correlations with good data fits to linearized plots (R 2  ≈ 0.900–0.999) that describe the arsenic sorption kinetics for both contaminated and pristine soils. The arsenic sorption data are generally best described by the Elovich model with smaller normalized standard deviations (Δq <5%) than PSO model. In addition, the surface binding to exchangeable and specific sorption of fresh arsenic (63–96%) sites has an impact on the overall low rate of As(V) sorption in the aged contaminated soils. Pristine soils "particularly ferralitic soils" show intra-particle diffusion and/or surface precipitation, which can contribute to a greater irreversibility of As(V) binding in soil. In contrast, the As(V) sorption occurred in the pristine sandy soil in a similar fashion to that of the aged contaminated soil, most likely due to both soil groups having limited strong binding sites. The detailed knowledge from this study provides new insights into the reclamation and management of As contaminated sites. Graphical abstract: Image 1 Highlights: Pseudo second order and Elovich models describe sorption kinetics for contaminated and pristine soils. Surface binding has an impact on low As sorption rate in aged contaminated soils. Surface complexation and diffusion control As sorption in pristine soils. Further addition of As to aged contaminated soils may lead to an increased As mobilisation.